Invasive aspergillosis successfully treated by combined antifungal therapy and immunosuppressive monotherapy two months following heart transplantation - Urbanowicz, Tomasz; Żabicki, Bartłomiej; Baszyńska-Wachowiak, Hanna; Straburzyńska-Migaj, Ewa; Juszkat, Robert; Grajek, Stefan; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Invasive aspergillosis is becoming increasingly prevalent, especially following transplantation. Invasive aspergillosis is associated with mortality. Successful therapy is related to early diagnosis and proper therapy. We present the case of a 61-year-old man suffering from invasive aspergillosis 2 months following heart transplantation. He was suffering from hypertrophic cardiomyopathy and he underwent orthotropic heart transplantation. He was readmitted to the Department of Cardiology 69 days following transplantation due to symptoms of productive cough for 5 days. It was accompanied by chest pain, shortness of breath, and fever up to 39°C. He was slightly cyanotic and confused on physical examination. The patient’s status deteriorated within the following 2 days. On bronchoscopic specimen examinations Aspergillus mould filaments were detected and the serum galactomannan index was 12.162. His blood saturation decreased to 85%. C-reactive protein serum level increased to 273 mg/l. The patient was admitted to the intensive care unit and intubated due to severe respiratory insufficiency. Computed tomography revealed massive, mostly homogeneous consolidation. The patient was treated with 200 mg of voriconazole and 50 mg of caspofungin daily. Caspofungin therapy was continued for 23 days and voriconazole was administered parenterally for 62 days. Voriconazole therapy was continued orally for 9 months. During combined antifungal therapy, the galactomannan serum index constantly decreased from 12.1 to 0.33 (end-point of caspofungin therapy) and to 0.23 (end-point of voriconazole parenteral administration). His immunosuppressive therapy was limited to calcineurin inhibitor (tacrolimus) monotherapy. Post-treatment imaging 9 months after diagnosis confirmed the efficacy of therapy as a lack of pulmonary infiltration associated with left apical peribronchial scarring as a result of treatment. The present case proved the efficiency of combined (voriconazole and caspofungin) antibiotic therapy in invasive pulmonary aspergillosis. Computed tomography findings followed by the serum galactomannan index are useful tools for early diagnosis. Additional modification of the immunosuppressive regimen can be performed safely in the early postoperative period in case of severe infection.